A spectroscopic database for water vapor between 5850 and 8340 cm−1. (August 2016) - Mikhailenko, S.N.; Kassi, S.; Mondelain, D.; Gamache, R.R.; Campargue, A.
Abstract: An accurate and complete empirical spectroscopic database is constructed for natural water in the 5850–8340 cm −1 near infrared region (1.71–1.20 µm). The global list includes more than 46, 500 transitions of the six most abundant isotopologues (H2 16 O, H2 18 O, H2 17 O, HD 16 O, HD 17 O, HD 18 O) in natural isotopic abundance with intensity greater than 1×10 −29  cm/molecule. All line positions were obtained by difference of empirically determined energy values. These empirical determinations are mostly based on extensive investigations of water vapor spectra by high-sensitivity CRDS complemented with literature data. In particular, the sets of energy levels of the minor isotopologues have been significantly enlarged from very recent analysis of CRDS spectra of D, 18 O and 17 O enriched water samples. The empirical line positions were associated to experimental intensity values from the literature obtained by FTS for the strong lines and CRDS for weaker lines. The list is made mostly complete by including a large number of weak transitions not yet detected, with empirical positions calculated from empirical levels associated with variational intensities. Air- and self-broadening coefficients and air-induced line shifts have been added to each transition using the most recent version of the algorithm used for the HITRAN and GEISA databases. Examples of comparison of CRDS spectra to simulations based on the HITRAN2012 list illustrate the advantages of our database. The relative merit of experimental and variational line intensities is discussed. A separate line list combining empirical line positions and variational intensities is provided. Future improvements from combination of experimental and variational intensities are suggested. Graphical abstract: Highlights: A spectroscopic database is constructed for natural water between 5850 and 8340 cm −1 . It includes 48, 009 transitions and correct deficiencies of the HITRAN line list. Line positions are obtained from empirical energy levels. Intensities are measured values by FTS or CRDS, when available. Air- and self-broadening coefficients and air-induced line shifts have been added.